TEKNOLOGI PENGOLAHAN LIMBAH PERTANIAN SEBAGAI PAKAN TERNAK RUMINANSIA DI KECAMATAN WAEAPO KABUPATEN BURU - Marna Eoh; Lea Marylin Rehatta; Muhammad Arif Basyari (MARSEGU : Jurnal Sains dan Teknologi, 2025)
This study aims to evaluate the extent of agricultural waste utilization and its usage techniques by livestock farmers. The survey method was applied through direct face-to-face meetings with respondents and direct observation in the field with 30 respondents selected by purposive sampling representing three villages in Waeapo District (Wanareja, Waenetat, Waekasar). The results of the study showed that agricultural waste from food crops, such as rice straw, can be utilized as ruminant livestock feed by 53.00%, some of the agricultural waste is processed into hay. As many as 53.00% of livestock farmers have been able to apply technology to manage agricultural waste into feed, especially skilled in making hay.